2015
DOI: 10.1016/j.bone.2015.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between frailty index of deficit accumulation and fracture risk assessment tool (FRAX) in prediction of risk of fractures

Abstract: A frailty index (FI) of deficit accumulation could quantify and predict the risk of fractures based on the degree of frailty in the elderly. We aimed to compare the predictive powers between the FI and the fracture risk assessment tool (FRAX) in predicting risk of major osteoporotic fracture (hip, upper arm or shoulder, spine, or wrist) and hip fracture, using the data from the Global Longitudinal Study of Osteoporosis in Women (GLOW) 3-year Hamilton cohort. There were 3985 women included in the study, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 48 publications
1
27
0
2
Order By: Relevance
“…Nevertheless, the absolute FI measures from the previous year were significantly related with increased risk of MOF, falls, and death in the following year (Tables and 4). Compared with the significant associations between the baseline FI and risk of adverse health outcomes during the 3‐year follow‐up, which had been published elsewhere, this study also found that the FI in the previous year was positively related with risk of fractures, falls, and death in the following 12 months. These findings reinforced the concept of the FI that compared with her peers, an elderly individual with more deficits was always more likely to experience adverse health outcomes independently of age, even though the outcomes were evaluated using annual short‐term intervals.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Nevertheless, the absolute FI measures from the previous year were significantly related with increased risk of MOF, falls, and death in the following year (Tables and 4). Compared with the significant associations between the baseline FI and risk of adverse health outcomes during the 3‐year follow‐up, which had been published elsewhere, this study also found that the FI in the previous year was positively related with risk of fractures, falls, and death in the following 12 months. These findings reinforced the concept of the FI that compared with her peers, an elderly individual with more deficits was always more likely to experience adverse health outcomes independently of age, even though the outcomes were evaluated using annual short‐term intervals.…”
Section: Discussionsupporting
confidence: 63%
“…All the models were adjusted for age. Results were reported using the per‐0.10 increment of the FI change and the FI absolute measures …”
Section: Methodsmentioning
confidence: 99%
“…Some studies described frailty using the Frailty Index, an accumulated health deficit model, and examined fracture risk according to graded frailty status [20,21]. These studies could not be incorporated in the meta-analysis only because they did not dichotomize (frailty and nonfrailty) or trichotomize (frailty, prefrailty, and non-frailty) frailty status.…”
Section: Discussionmentioning
confidence: 97%
“…Fried et al defined frailty as having three or more of the five criteria: unintentional weight loss, self-reported exhaustion, weakness, slow walking speed, and low physical activity in the Cardiovascular Health Study (CHS) [13]. Whereas fracture was not examined in this study, several studies have later investigated associations between frailty and fractures and inconsistently shown significant and non-significant results [14][15][16][17][18][19][20][21]. These studies used various frailty criteria and different types of fractures, which makes it difficult to reach the conclusions on frailty as a predictor of fractures.…”
Section: Introductionmentioning
confidence: 96%
“…This questionnaire was designed on the basis of the characteristics of very elderly males, risk factors for osteoporosis [22], and referring to the WHO Fracture Risk Assessment Tool (FRAX ® ) [23]. The detailed questionnaire is as follows ( Table 1).…”
Section: Surveys Of Lifestyle Factors and Underlying Chronic Diseasesmentioning
confidence: 99%